INOVASI AGRARIS: MEWUJUDKAN PEMBERDAYAAN PEREMPUAN TANI MELALUI PEMANFATAN LAHAN PEKARANGAN DAN SOCIAL CAPITAL - Sari, Yessi Avita; Fasa, Muhammad Iqbal; Noviarita, Heni; Angraeni, Erike (JURNAL ILMIAH EDUNOMIKA, 2024)
The use of homestead land has a vital role in increasing local food production and is an important strategy in maximizing the use of this land, such as good planning and crop diversification. Apart from that, the role of the Women Farmers Group (KWT) in providing education and training to local communities to manage their homesteads effectively is the focus of the research. The main objective of this research is to understand effective strategies for maximizing homestead productivity, with a focus on careful planning and crop diversification. In addition, this research considers the application of social capital as a key factor in increasing access to information, technology and other resources. The research method used is a qualitative type with library research measuring instruments. The research results highlight the need for empowerment through KWT and the use of social capital to support sustainable agriculture and improve community welfare through better agricultural efficiency.